2015
DOI: 10.1111/1750-3841.12894
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Antibrowning, Heat Treatment and Modified‐Atmosphere Packaging to Extend the Shelf Life of Fresh‐Cut Lotus Root

Abstract: This work aimed to determine the effects of different concentrations of antibrowning treatments (that is, distilled water [DW], 1% ascorbic acid [AA], 0.5% chamomile [CM], and 1% AA + 0.5% CM) and heat-treatment (55 °C for 45 s) combined with packaging under 4 different modified-atmosphere gas compositions (that is, air, vacuum, 100% CO2 , 50% CO2 /50% N2 ) on the quality and microbiological characteristics of fresh-cut lotus root. The quality characteristics (that is, color, weight loss, texture, pH, polyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…According to these results, CO 2 gas packaging at high concentration (100% CO 2 gas) was effective in inhibiting the levels of microorganisms in grapes, soybean sprouts, and lotus roots during storage. Similar results from another study showed that MAP using CO 2 gas, following treatment with a chemical such as ascorbic acid and chamomile extract, was effective in delaying the growth of total aerobic bacteria, total coliform, and yeast and mold during storage for 21 days (Son, Hyun, Lee, Lee, & Moon, 2015). Hyun et al (2015) also observed that MAP using CO 2 gas was more effective in maintaining reduced levels of total mesophilic bacteria on fresh cabbage and radish sprouts during storage for 21 days, and their reduction levels were 1.55 and 2.26 log CFU/g compared to control, respectively.…”
Section: Microbial Populationssupporting
confidence: 69%
“…According to these results, CO 2 gas packaging at high concentration (100% CO 2 gas) was effective in inhibiting the levels of microorganisms in grapes, soybean sprouts, and lotus roots during storage. Similar results from another study showed that MAP using CO 2 gas, following treatment with a chemical such as ascorbic acid and chamomile extract, was effective in delaying the growth of total aerobic bacteria, total coliform, and yeast and mold during storage for 21 days (Son, Hyun, Lee, Lee, & Moon, 2015). Hyun et al (2015) also observed that MAP using CO 2 gas was more effective in maintaining reduced levels of total mesophilic bacteria on fresh cabbage and radish sprouts during storage for 21 days, and their reduction levels were 1.55 and 2.26 log CFU/g compared to control, respectively.…”
Section: Microbial Populationssupporting
confidence: 69%
“…The enzyme activity that results in browning may additionally destroy some bioactive compounds, reducing the nutritional quality of lotus root. Many treatments have been researched and applied in attempt to inhibit browning and maintain quality of fresh-cut lotus root, including heat in conjunction with anaerobic conditions (Son et al, 2015), carbon monoxide (CO) fumigation (Zhang et al, 2013), hydrogen sulfide (H2S) fumigation (Sun et al, 2015), chitosan-based coating (Xing et al, 2010), aqueous chlorine dioxide (ClO2), ascorbic acid, erythorbic acid, citric acid, L-cysteine, NaHSO3 and modified atmosphere (Du et al, 2009;Jiang et al, 2014;Lee & Eun, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…However, during processing and storage, fresh-cut lotus root is highly susceptible to deterioration, which directly affects its quality and shelf life. The main reason for the decline in quality of fresh-cut products has been enzymatic browning (Eissa et al, 2006;Pma, 2006;Son et al, 2015).…”
mentioning
confidence: 99%
“…At present, the methods for controlling the browning of lotus root mainly include chemical treatment (Kwon and Baek, 2014;Lu et al, 2007), modified atmosphere (MA) packaging (Cheng et al, 2015), vacuum packaging (Son et al, 2015;Xing et al, 2012), heat treatment (Tsouvaltzis et al, 2011), and low-temperature storage (Min et al, 2017). Among these, vacuum packaging is a natural preservation method that can greatly enhance the shelf life and overall quality of fresh produce (Mcdonald and Sun, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation